In situ catalyzing gas conversion using char as a catalyst/support during brown coal gasification - Wang, Y.; Sun, J.; Zhang, H.; Chen, Z.; Lin, X.; Zhang, Shu; Gong, W.; Fan, M. (American Chemical Society, 2015)
© 2015 American Chemical Society. The purpose of this study was to demonstrate the effectiveness of in situ gas conversion using char as a catalyst/catalyst support in the gasification of Shengli brown coal in an entrained-flow reactor. The catalytic steam gasification of brown coal was also conducted with a feedstock of coal and catalyst mixed under the same conditions. With brown coal char being activated, both calcium and nickel supported on activated char were used as catalysts in these two types of study. The results showed that all catalysts increased H 2 concentrations and had good activity for reforming the gas product from brown coal gasification. As for the effects on promoting H 2 production, the Ca/char and Ni/char catalysts showed higher catalytic activity than char alone in brown coal steam gasification. Physical structure and X-ray diffraction results showed that activated char was a better catalyst carrier, in which O-containing groups played a significant role in syngas reforming, and the disordered structure determined the catalytic activity of the catalyst in the process of brown coal gasification.